DEMOKRASI DAN PEMBANGUNAN - Witianti, Siti (JWP (Jurnal Wacana Politik), 2016)
The relations between democray and development has become wide discussion since world warÂ two until now. The question rised whether democracy supports development or developmentÂ supports democracy both in central and local level. Democracy has been choosed in manycountries. Democracy marked by participation needed in development. Furthermore, democracyÂ needs better peopleâs capacity which only can be done in the development process. ComprehensiveÂ development concept stresses on the people. People become subject and object in the development.Â Peopleâs participation makes the result of development suits with the need of the people. There isÂ an opinion that comprehensive development process might support democratization process.